2020
DOI: 10.1186/s13244-020-0836-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of multi-material artifact reduction (MMAR) technique in Revolution CT to reduce metallic dental artifacts

Abstract: Background: This study aimed to explore the performance of Revolution CT virtual monoenergetic images (VMI) combined with the multi-material artifact reduction (MMAR) technique in reducing metal artifacts in oral and maxillofacial imaging. Results: There were significant differences in image quality scores between VMI + MMAR images and VMI+MARS (multiple artifact reduction system) images at each monochromatic energy level (p = 0.000). Compared with the MARS technology, the MMAR technology further reduced metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The extent of these are influenced by various parameters such as material of the implants, tube voltage and current as well as reconstruction parameters 4 . Several studies employing dual energy CT systems based on energy integrating detectors have shown that the reconstruction of virtual monoenergetic images (VMI) can help to decrease the extent of implant associated artifacts 2,[5][6][7][8] .…”
mentioning
confidence: 99%
“…The extent of these are influenced by various parameters such as material of the implants, tube voltage and current as well as reconstruction parameters 4 . Several studies employing dual energy CT systems based on energy integrating detectors have shown that the reconstruction of virtual monoenergetic images (VMI) can help to decrease the extent of implant associated artifacts 2,[5][6][7][8] .…”
mentioning
confidence: 99%
“…In another study written by Wei et al [ 13 ], they reported, “we found that compared to the 64-slice Discovery CT virtual monoenergetic images combined with MARS technique for image reconstruction, the 256-slice Revolution CT combined with Multi-material artifact reduction technique for image reconstruction is better to reduce metal artifacts and background standard deviation” [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…See the above-mentioned paragraph and Figure 14); • Metal artifact reduction algorithms. They replace the metal trace region with neighbouring data (also known as iterative reconstruction techniques) (Figure 20) [54].…”
mentioning
confidence: 99%
“…See the above-mentioned paragraph and Figure 14); • Metal artifact reduction algorithms. They replace the metal trace region with neighbouring data (also known as iterative reconstruction techniques) (Figure 20) [54]. These three different strategies can also be used in combination to improve the dental artifact reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation